2020
DOI: 10.1002/ehf2.12798
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and sleep‐disordered breathing: susceptibility to reduced muscle strength and preclinical congestion (SICA‐HF cohort)

Abstract: Aims Increased sympathetic activation in patients with heart failure (HF) and sleep-disordered breathing (SDB) provokes cardiac decompensation and protein degradation and could lead to muscle wasting and muscle weakness. The aim of this study was to investigate the differences in body composition, muscle function, and the susceptibility of preclinical congestion among patients with HF and SDB compared with those without SDB. Methods and results We studied 111 outpatients with stable HF who were enrolled into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…There were a limited number of studies that investigated the association between OSA and sarcopenia. Bekfani T et al found a positive correlation between sleep-disordered breathing and low muscle strength in patients with heart failure [14]. However, Fernandes et al indicated that OSA was not associated with sarcopenia in a population of patients with non-dialyzed chronic kidney disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…There were a limited number of studies that investigated the association between OSA and sarcopenia. Bekfani T et al found a positive correlation between sleep-disordered breathing and low muscle strength in patients with heart failure [14]. However, Fernandes et al indicated that OSA was not associated with sarcopenia in a population of patients with non-dialyzed chronic kidney disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…The article on muscle wasting cited in the HF guidelines suggests cut-off points used to detect the presence of sarcopenia as the appendicular skeletal mass index values of 7.0 kg/m 2 for men and 5.5 kg/m 2 for women [ 7 ]. It has been shown that patients with sarcopenic HF have reduced exercise capacity [ 8 , 9 ], reduced quality of life, endothelial dysfunction [ 10 ], and reduced appetite [ 11 ] among other detrimental consequences [ 12 ]. Sarcopenia also has independent prognostic value in patients with HF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with symptomatic or decompensated HF, the prevalence of sleep apnea ranges up to 80%. More than half of these individuals suffer from OSA [16,17]. Sleep apnea, whether in the presence or absence of HF, is associated with a higher risk of negative cardiovascular outcomes, including aggravation of HF-related symptoms, increased hospitalizations, and higher mortality rates.…”
Section: Introductionmentioning
confidence: 99%